Faktor-Faktor Yang Berhubungan Dengan Kinerja Kader Posyandu - Rita Afni (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2015)
Background: Performance posyandu cadres is something that can be done by a cadre of neighborhood healthcenter in accordance with its duties and functions are influenced by the attitudes, knowledge and skills which havereceived special training from the local health center to implement, maintain and develop the existing IHC activitiesin the area voluntarily.Objective: The purpose of this study is to know the factors that relate to the performance of cadres posyandu inPuskesmas Gunung Sahilan Kec. Kampar Kiri .Metode: This study used quantitative analytical method, the cross-sectional design. The population in this studywere all health cadres in 18 neighborhood health center in Puskesmas Mount Sahilan District of Kampar Kiri in2012, amounting to 114 people. The sample in this study was the total population, so the sample in this study were114 cadres.Result: The results obtained are of young age of 45 respondents who most of the cadres Posyandu have a goodperformance as many as 24 respondents (53.3%) with significant value of 0.003 (p value < 0.05), from 67α respondents had education Low largely posyandu cadres have poor performance as many as 50 respondents (74.6%)with significant value of 0.009 (p value < 0.05), from 52α respondents who said coaching is not good most of thecadres Posyandu have performance not good as many as 37 respondents (71.2%) with significant value of 0.210(p value> ), from 68 respondents have a negative attitude mostα0.05 of the cadres Posyandu have poor performance as many as 52 respondents (76, 5%) with significant value of 0.002 (p value < 0.05), and 58α respondentswho either do not have the perception that the majority of cadres Posyandu have poor performance as many as 41respondents (70.7%) with significant value for 0.190 (p value> )α0.05Conclusion: The conclusion of this study is a significant relationship between age, education and attitude.Keywords: Performance, Posyandu cadres